2019
DOI: 10.1093/nar/gkz1028
|View full text |Cite
|
Sign up to set email alerts
|

SEA version 3.0: a comprehensive extension and update of the Super-Enhancer archive

Abstract: Super-enhancers (SEs) are critical for the transcriptional regulation of gene expression. We developed the super-enhancer archive version 3.0 (SEA v. 3.0, http://sea.edbc.org) to extend SE research. SEA v. 3.0 provides the most comprehensive archive to date, consisting of 164 545 super-enhancers. Of these, 80 549 are newly identified from 266 cell types/tissues/diseases using an optimized computational strategy, and 52 have been experimentally confirmed with manually curated references. We now support super-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 23 publications
0
51
1
Order By: Relevance
“…(F) Genomic coordinates of common histone modifications in HeLa cells were determined from ENCODE ChIP-seq data. Coordinates of “super enhancers” in HeLa cells were extracted from the SEA 3.0 database [ 71 ]. Frequency of integration within 1 kb of these locations was calculated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(F) Genomic coordinates of common histone modifications in HeLa cells were determined from ENCODE ChIP-seq data. Coordinates of “super enhancers” in HeLa cells were extracted from the SEA 3.0 database [ 71 ]. Frequency of integration within 1 kb of these locations was calculated.…”
Section: Resultsmentioning
confidence: 99%
“…Genomic locations of RNA polymerase II binding and histone modifications was extracted from ENCODE data sets (Pol II: ENCFF246QVY; H3K27Ac: ENCFF113QJM; H3K9me3: ENCFF712ATO; H3K36me3: ENCFF864ZXP; H3K4me3: ENCFF862LUQ). Genomic coordinates of “super enhancers” in HeLa cells were extracted from the SEA 3.0 database [ 71 ]. Distance of integration to nearest feature was calculated using BedTools [ 72 ].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, as a single histone mark is not a reliable CRM predictor, a great deal of efforts have been made to predict CRMs based on multiple histone marks and chromatin accessibility (CA) data from the same cell/tissue types using various machine-learning methods, including hidden Markov models(Ernst & Kellis, 2012), dynamic Bayesian networks(Hoffman et al, 2013), time-delay neural networks(Firpi, Ucar, & Tan, 2010), random forest(Rajagopal et al, 2013), and support vector machines (SVMs)(Kleftogiannis, Kalnis, & Bajic, 2015). Many enhancer databases have also been created either by combining results of multiple such methods(Ashoor, Kleftogiannis, Radovanovic, & Bajic, 2015; Fishilevich et al, 2017; Zerbino, Wilder, Johnson, Juettemann, & Flicek, 2015), or by identifying overlapping regions of CA and histone mark tracks in the same cell/tissue types(Chen et al, 2020; Cheneby, Gheorghe, Artufel, Mathelier, & Ballester, 2018; Gao & Qian, 2020; Kang et al, 2019; G. Zhang et al, 2018). In particular, most recently, the ENCODE phase 3 consortium(Moore et al, 2020) identified 926,535 candidate cis -regulatory elements (cCREs) based on overlaps between millions of DNase I hypersensitivity sites (DHSs)(Thurman et al, 2012) and transposase accessible sites (TASs)(Buenrostro, Giresi, Zaba, Chang, & Greenleaf, 2013), active promoter histone mark H3K4me3(Aday, Zhu, Lakshmanan, Wang, & Lawson, 2011) peaks, active enhancer mark H3K27ac(Creyghton et al, 2010) peaks, and insulator mark CTCT(Kim et al, 2007) peaks in a large number of cell/tissue types.…”
Section: Introductionmentioning
confidence: 99%
“…More than 80,000 super-enhancers (combined numbers for the mouse and human genome) can be accessed through the online dbSuper database [28]. An updated version of the Super Enhancer Archive (SEA 3.0) provides another entry point [29], but this database was unfortunately offline when we were drafting this manuscript (Supplementary Table 1).…”
Section: Identifying Putative Regulatory Elementsmentioning
confidence: 99%
“…[28] http://sea.edbc.org SEA version 3.0 was updated in 2019 and promises to be a comprehensive resource that stores predicted super-enhancers and enhancers from 11 different species and more than 200 types of cells, tissues and diseases. [29] https://tabula-muris-senis.ds.czbiohub.org/ A large compendium of single cell transcriptome data from the model organism Mus musculus that contains scRNAseq datasets of 23 organs and tissues, including the mammary gland at 6 different timepoints (1 month, 3 months, 18 months, 21 months, 24 months, 30 months). This online dataset explicitly includes stromal cells and other cell types from the supportive tissue (e.g.…”
Section: Tool Description Referencementioning
confidence: 99%